2008
DOI: 10.1073/pnas.0800454105
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism of the erythropoietin gene in severe diabetic eye and kidney complications

Abstract: Significant morbidity and mortality among patients with diabetes mellitus result largely from a greatly increased incidence of microvascular complications. Proliferative diabetic retinopathy (PDR) and end stage renal disease (ESRD) are two of the most common and severe microvascular complications of diabetes. A high concordance exists in the development of PDR and ESRD in diabetic patients, as well as strong familial aggregation of these complications, suggesting a common underlying genetic mechanism. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
193
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(214 citation statements)
references
References 35 publications
14
193
2
5
Order By: Relevance
“…This study provided the first evidence that EPO acts on the angiogenic pathway independently from VEGF and is more strongly correlated with the presence of PDR than VEGF (Watanabe et al 2005). Subsequent studies have shown genetic mutations can increase EPO expression and this is associated with increased risk of PDR and related condition in patients and in animals (Tong et al 2008;Chen et al 2009;Xiong et al 2009;Abhary et al 2010).…”
Section: Angiogenic Mechanisms In Proliferative Diabetic Retinopathymentioning
confidence: 86%
“…This study provided the first evidence that EPO acts on the angiogenic pathway independently from VEGF and is more strongly correlated with the presence of PDR than VEGF (Watanabe et al 2005). Subsequent studies have shown genetic mutations can increase EPO expression and this is associated with increased risk of PDR and related condition in patients and in animals (Tong et al 2008;Chen et al 2009;Xiong et al 2009;Abhary et al 2010).…”
Section: Angiogenic Mechanisms In Proliferative Diabetic Retinopathymentioning
confidence: 86%
“…The change of genotype (TT in replacement of GG) might enhance the transcription of the EPO gene as EPO was present in higher amount in vitreous fluid, even in samples that were collected from non-diabetic individuals. 56 We have illustrated with reasonable evidence on the role, mechanism, and interaction of EPO as a therapeutic and pathological agent under different pre-clinical settings for different models of ocular disorders. These will be the basis for extrapolation to rational strategies for EPO application and administration for ocular disorders.…”
Section: The Role Of Epo In the Eyementioning
confidence: 87%
“…39,53 This study proposed that NO stimulation was regulated by the heterotrimeric interaction between EPOR/βcR/VEGF-R2 upon binding of EPO to EPOR/βcR. 39,[51][52][53][54][55] Meanwhile, studies have reported that genetic polymorphism in the EPO gene may be a pathogenic factor for acquiring risk of proliferative DR. 56 Katsura et al 55 showed that vitreous EPO was present in significantly higher amount in proliferative DR patients than in macular hole patients who had no retinopathy. The authors further showed the high EPO concentration was not induced by systemic anemia.…”
Section: The Role Of Epo In the Eyementioning
confidence: 99%
“…However, contrary to these findings, the number of recorded cases of non-coding mutations linked to human diseases has been growing rapidly. HTRA1 promoter mutation has been linked to macular degeneration [36], PKLR promoter mutation to pyruvate kinase deficiency [37], erythropoietin promoter mutation to diabetic eye and kidney complications [38]. Multiple other promoter mutations have been also associated with different diseases [5].…”
Section: Importance Of Regulatory Elements In Human Health: Diseases mentioning
confidence: 99%